The influence of letterboard media on reading interest elementary school students in lower grades - Ahmad Zamhari; Eka Putri Alisya; Dewi Agustina; Dinda Novitasari; Aulia Nurrahmah (ARKA INSTITUTE, 2023)
This study aims to develop a letter board learning media to increase elementary school students' interest in reading, especially in low grades. The type of research used is research and development (ADDIE). Initial findings on the learning media used by the teacher are only printed media in the form of textbooks. Thus, making students less enthusiastic and easily bored when told to read, and the learning process becomes very monotonous. Based on the results of the preliminary study, the authors intend to develop a Letter Board product to increase interest in reading for low grade elementary school students. The Letter Board learning media is tested by media experts. The validation results by media experts obtained a score of 94.48% which is included in the very high category and is feasible to implement.